Response of green chiretta to different bio-fertilizers and their effect on phosphorus availability in the soil - Sukyankij, Saychol; Phun-iam, Mutchima; Panich-pat, Thanawan (Journal of Degraded and Mining Lands Management, 2024)
When cultivating medicinal plants, the use of chemical substances such as pesticides and chemical fertilizers should be avoided, as these can be contaminated with hazardous substances. Bio-fertilizers are a good alternative for growing herbs, as they are produced from organic materials that contain fewer hazardous substances. The aim of this study was to investigate the effects of different bio-fertilizers on growth, yield, andrographolide content, nutrient accumulation, and different pigments in green chiretta. In addition, the effectiveness of bio-fertilizers on the convertible phosphorus content in the soil was investigated. The experimental design was a completely randomized design (CRD) with four treatments and four replicates. The details of the experiment were 1) control (no bio-fertilizer), 2) phosphate-solubilizing microorganisms (PSMs), 3) plant growth promoter, and 4) mycorrhiza. The findings revealed that the application of PSMs provided the highest leaf dry weight (yield) of green chiretta (20.8±3.58 g/plant). This treatment also gave the highest chlorophyll a, b and total chlorophyll content (699±70, 178±24, 880±94 mg/sqm, respectively) and andrographolide yield (0.38±0.06 g/plant). Regarding the phosphorus content in the soil, the PSMs application showed the highest available phosphorus and the highest phosphorus activation coefficient (PAC) in the soil, namely 52.0±4.76 mg/kg and 4.22±0.32 percent, respectively. These results indicate that the use of PSMs as a bio-fertilizer is most suitable for the cultivation of green chiretta, especially when this plant grows on acid sulfate soils.